Pseudogap of Metallic Layered Nickelate R2-xSrxNiO4 (R = Nd, Eu) Crystals Measured Using Angle-Resolved Photoemission Spectroscopy - Uchida, Masaki; Ishizaka, Kyoko; Hansmann, Philipp; Kaneko, Yoshio; Ishida, Yukiaki; Yang, Xiaoping; Kumai, Reiji; Toschi, Alessandro; Onose, Yoshinori; Arita, Ryotaro; Held, Karsten; Andersen, O. K.; et al. (Physical Review Letters, 2011)
We have investigated charge dynamics and electronic structures for single crystals of metallic layered nickelates, R2-xSrxNiO4 (R = Nd, Eu), isostructural to La2-xSrxCuO4. Angle-resolved photoemission spectroscopy on the barely metallic Eu0.9Sr1.1NiO4 (R = Eu, x = 1.1) has revealed a large hole surface of x(2) - y(2) character with a high-energy pseudogap of the same symmetry and comparable magnitude with those of underdoped (x < 0.1) cuprates, although the antiferromagnetic interactions are 1 order of magnitude smaller. This finding strongly indicates that the momentum-dependent pseudogap feature in the layered nickelate arises from the real-space charge correlation.
CRIS-Team WoS Importer:2020-02-19